2013
DOI: 10.5056/jnm.2013.19.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Technique of Functional and Motility Test: How to Perform Antroduodenal Manometry

Abstract: Antroduodenal manometry is one of the methods to evaluate stomach and duodenal motility. This test is a valuable diagnostic tool for gastrointestinal motility disorders especially small intestinal pseudo-obstruction which is difficult to make definite diagnosis by clinical manifestations or radiologic findings. Manometric findings that have no evidence of mechanical obstruction and suggestive of pseudo-obstruction with neuropathy or myopathy can avoid unnecessary surgery and the treatment can be directly targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 54 publications
2
58
0
2
Order By: Relevance
“…It has been hypothesized that severe mucosal damage and inflammation may be more strictly related to gastrointestinal motility derangement in CD [11]. However, this is discordant with the clinical situation, where CD can present with dyspeptic symptoms without signs or symptoms of severe inflammation [13]. …”
Section: Possible Mechanisms Involved In Motility Alterations In CD Amentioning
confidence: 86%
See 1 more Smart Citation
“…It has been hypothesized that severe mucosal damage and inflammation may be more strictly related to gastrointestinal motility derangement in CD [11]. However, this is discordant with the clinical situation, where CD can present with dyspeptic symptoms without signs or symptoms of severe inflammation [13]. …”
Section: Possible Mechanisms Involved In Motility Alterations In CD Amentioning
confidence: 86%
“…This constitutes a valuable method to assess gastroduodenal motility, and consists of the measurement of motor activity by the insertion of a manometric PVC catheter just beyond the angle of Treitz [13]. Intraluminal pressures are recorded using high-resolution solid-state transducers or water-perfused systems.…”
Section: Brief Overview Of Methods To Assess Gut Motilitymentioning
confidence: 99%
“…Using antroduodenal manometry (ADM), other groups have demonstrated the use of duodenal motility patterns to make diagnoses that could not be made empirically from the clinical history alone (19). To date, the link between symptom severity and physiologic abnormalities in gastroparesis has proven elusive, with poor correlation continually observed between symptoms and gastric transit and pressure parameters (1517).…”
Section: Discussionmentioning
confidence: 99%
“…The recent advent of solidstate high-resolution ADM catheters may address some of these difficulties in future. 29 WGS can be used to estimate SBTT and this technique has been compared to WMC in a small study of 10 subjects, in which the two procedures were concurrently undertaken. 30,31 It was shown that WMC measured small bowel contractions per min showed a positive correlation with percentage scintigraphic small bowel transit (r ¼ 0.69; p ¼ 0.05).…”
Section: Stomachmentioning
confidence: 99%